Lanthanide-Doped Luminescent Nanophosphors via Ionic Liquids - Sharma, Rahul Kumar; Ghosh, Pushpal (Frontiers in Chemistry, 2021)
Lanthanide (Ln3+) ion(s)-doped or rare-earth ion(s)-doped nanomaterials have been considered a very important class of nanophosphors for various photonic and biophotonic applications. Unlike semiconductors and organic-based luminescent particles, the optical properties of Ln3+-doped nanophosphors are independent of the size of the nanoparticles. However, by varying the crystal phase, morphology, and lattice strain of the host materials along with making core-shell structure, the relaxation dynamics of dopant Ln3+ ions can be effectively tuned. Interestingly, a judicious choice of dopant ions leads to unparallel photophysical dynamics, such as quantum cutting, upconversion, and energy transfer. Recently, ionic liquids (ILs) have drawn tremendous attention in the field of nanomaterials synthesis due to their unique properties like negligible vapor pressure, nonflammability, and, most importantly, tunability; thus, they are often called “green” and “designer” solvents. This review article provides a critical overview of the latest developments in the ILs-assisted synthesis of rare-earth-doped nanomaterials and their subsequent photonic/biophotonic applications, such as energy-efficient lighting and solar cell applications, photodynamic therapy, and in vivo and in vitro bioimaging. This article will emphasize how luminescence dynamics of dopant rare-earth ions can be tuned by changing the basic properties of the host materials like crystal phase, morphology, and lattice strain, which can be eventually tuned by various properties of ILs such as cation/anion combination, alkyl chain length, and viscosity. Last but not least, different aspects of ILs like their ability to act as templating agents, solvents, and reaction partners and sometimes their “three-in-one” use in nanomaterials synthesis are highlighted along with various photoluminescence mechanisms of Ln3+ ion like up- and downconversion (UC and DC).